(untitled) (Annals of Library and Information Studies, 2025)
The allopathic medical system, has practically taken over traditional medicine systems due to its evidence-based knowledge generation and documentation. Traditional medicine still faces challenges in proper information sharing and documentation. However, in the context of holistic medicine, the Complementary and Alternative System (CAM) is gaining importance in treating diseases like cancer and their management. The lack of a suitable mechanism for sharing and preserving knowledge has caused the knowledge of traditional medicine (know-how) to disappear. To address this, ICT and internet- based systems are being advocated, and libraries should focus on managing and preserving Indigenous Knowledge (IK). Librarians’ knowledge of information storage and retrieval is useful in the semantic web environment too. One of the limitations of a CAM-related information system is, the meaningful mapping with the modern medicine system. This constraint can be overcome by integrating various classification schemes that are used for traditional literature management. The most common controlled vocabularies used for the allopathic medicine system include Medical Subject Headings (MeSH) and Unified Medical Language System (UMLS), Tumour Neoplasm Metastases (TNM) and others. Some of the commonly used schemes for knowledge organisation in the web environment are taxonomies and ontologies. Now natural language processing (NLP) is gaining momentum for information retrieval. It needs to be used fruitfully for organising CAM literature. While dealing with disease data (patient records), modern medicine predominately uses International Classification Disease (ICD). A suitable mechanism for mapping the CAM system with the modern medicine records is likely to be useful for any information system for any given disease, including cancer (oncology). A meaningful integration of such techniques and tools is essential for developing an information system in CAM for disease management. Even though CAM is viewed as important in terms of a holistic medicine system, there are a few constraints; to name a few, the modern medicine system is based on an evidence-based approach, and thus proper information management about adverse drug reactions (ADR) is important. While there are some concerns and constraints in the use of CAM in comparison to the modern medicine system, which is based on an evidence-based system, proper information management about ADR, and recalibration of drugs dosage in terms of units of CAM with those of allopathy is necessary. This paper is an attempt to discuss the present status of cancer treatment and care with special reference to India. Additionally, how a CAM system can effectively become a part and parcel of the holistic medicine system. The slant is towards the information and knowledge management system. Useful studies from some of the other countries are also cited as success stories.